2020
DOI: 10.1111/add.14911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing the delivery of smoking cessation care in alcohol and other drug treatment centres: a cluster‐randomized controlled trial

Abstract: Aim Aims were to test the effectiveness of an organizational change intervention integrating smoking cessation treatment into usual alcohol and other drug (AOD) treatment, compared with usual care, on (1) 7‐day point prevalence abstinence (PPA) at 8 weeks follow‐up; (2) prolonged abstinence; (3) cigarettes smoked per day; (4) number of quit attempts; and (5) offer and use of nicotine replacement therapy (NRT). All outcomes were assessed at 8 weeks and 6.5 months follow‐up. Design Cluster‐randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…1). Twenty‐three studies [10,37–58] were RCTs (intervention n = 6593, control n = 5801). Three studies [59–61] were trials, but adopted a non‐randomized design (intervention n = 845, control n = 394).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Twenty‐three studies [10,37–58] were RCTs (intervention n = 6593, control n = 5801). Three studies [59–61] were trials, but adopted a non‐randomized design (intervention n = 845, control n = 394).…”
Section: Resultsmentioning
confidence: 99%
“…Post-discharge interventions were included in the majority of the trials (n = 23), with the exception of three [38,39,45] and five cohort studies [9,61,63,66,67]. Telephone calls were used in 14 studies [10,41,42,48,[50][51][52][54][55][56]58,60,61,67], ranging from one to 14 calls at time-points between 1 day and 9 months post-discharge.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Organizational change interventions have been associated with increased favorable attitudes toward treating tobacco use disorder in SUD treatment programs, use of NRT medications, client receipt of services from their programs or counselors, and a reduction client smoking prevalence and cigarettes smoked per day. 36,37 Furthermore, funding streams continue to serve as a barrier to the availability of smoking cessation services in SUD treatment programs. 34 Smoking cessation covered services have expanded with the expansion of Medicaid under the Affordable Care Act (ACA).…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a cluster randomised controlled trial, the Tackling Nicotine Together project. The trial protocol [14] and primary outcomes [15] are reported elsewhere. Briefly, AOD health‐care providers were recruited from 32 participating trial services and completed an online survey 6 months pre‐intervention implementation (August to September 2014) and 18 months post‐intervention implementation (October 2016).…”
Section: Methodsmentioning
confidence: 99%